From data to diagnosis: leveraging deep learning in IoT-based healthcare - Miracle A. Atianashie; Chukwuma Chinaza Adaobi (Academia Medicine)
In the evolving landscape of healthcare, the integration of deep learning within the Internet of Things (IoT) presents transformative potentials for medical diagnostics and patient care. This article explores the advanced architectures of deep learning and their application in healthcare IoT, emphasizing the enhancement of disease prediction models, medical image analysis, and real-time health monitoring systems. Deep learning’s capacity to handle vast and complex datasets by extracting high-level features and enabling predictive analytics is particularly beneficial in healthcare, where timely and accurate diagnosis can significantly influence treatment outcomes. Furthermore, the implementation of deep learning technologies in healthcare IoT has proven effective in the early detection of critical health conditions, including cancer and neurodegenerative diseases, through sophisticated analysis of medical images and physiological data. This article also discusses the pivotal role of Graphics Processing Units (GPUs)-accelerated computing and the expertise of medical professionals in refining deep learning models for clinical applications. Despite these advancements, challenges remain such as data privacy, interoperability of diverse systems, and the computational demands of processing large-scale data. Ethical and legal considerations are also critical as the deployment of artificial intelligence in healthcare necessitates careful consideration of patient consent and data security. The future of deep learning in healthcare IoT is geared toward enhancing data security, improving device integration, and creating patient-centric models through innovative technologies such as blockchain and edge computing. This article advocates for a collaborative approach to overcome barriers and accelerate the adoption of these technologies in mainstream healthcare settings.